2013
DOI: 10.3357/asem.3503.2013
|View full text |Cite
|
Sign up to set email alerts
|

Military Aircrew and Noise-Induced Hearing Loss: Prevention and Management

Abstract: Modern-day high performance aircraft are more powerful, more efficient, and, unfortunately, frequently produce high noise levels, resulting in noise-induced hearing loss (NIHL) in military aircrew. Military pilots are required to perform many flight duties correctly in the midst of many challenges that may affect mission completion as well as aircraft and aircrew safety. NIHL can interfere with successful mission completion. NIHL may also require aircrew to be downgraded from flying duties, with the incumbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…Free radicals and oxidative stress play an important role in the pathogenesis of NIHL. Previous studies have confirmed that noise stimulation leads to the production of a wide range of free radicals in cochlear tissues and neurons, such as hydroxyl, hydrogen peroxide, superoxide anion, and NO-related free radicals (Rajguru, 2013;Tuerdi et al, 2017;Han et al, 2018). The free radicals produced by noise-induced oxidative stress can destroy proteins, lipids, and DNA when they exceed the endogenous antioxidant capacity, triggering cell death due to necrosis and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Free radicals and oxidative stress play an important role in the pathogenesis of NIHL. Previous studies have confirmed that noise stimulation leads to the production of a wide range of free radicals in cochlear tissues and neurons, such as hydroxyl, hydrogen peroxide, superoxide anion, and NO-related free radicals (Rajguru, 2013;Tuerdi et al, 2017;Han et al, 2018). The free radicals produced by noise-induced oxidative stress can destroy proteins, lipids, and DNA when they exceed the endogenous antioxidant capacity, triggering cell death due to necrosis and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Prevention and treatment are two strategies used against NIHL. However, prevention strategies, including hearing conservation programs, education, and ear protection devices are ineffective because of their lack of efficiency and accessibility (Chen and Tsai, 2003;Rajguru, 2013;Sekhar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen is bioavailable, known to be clinically safe, blood-brain barrier permeant, and can achieve brain levels that are 21% of plasma levels (Imai et al, 2001 ). A phase I safety study using doses of 200–1600 mg was conducted and has led to a phase II clinical trial for noise-induced hearing loss (Lynch and Kil, 2009 ; Rajguru, 2013 ). A single oral dose of 100 mg/kg of ebselen in rat yields serum values of 4–5 μM (Salom et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%